2005
DOI: 10.4049/jimmunol.175.7.4184
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: Activation of the Aryl Hydrocarbon Receptor by 2,3,7,8-Tetrachlorodibenzo-p-dioxin Generates a Population of CD4+CD25+ Cells with Characteristics of Regulatory T Cells

Abstract: Activation of the aryl hydrocarbon receptor (AhR) by its most potent ligand, 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD), leads to immune suppression in mice. Although the underlying mechanisms responsible for AhR-mediated immune suppression are not known, previous studies have shown that activation of the AhR must occur within the first 3 days of an immune response and that CD4+ T cells are primary targets. Using the B6-into-B6D2F1 model of an acute graft-vs-host response, we show that activation of AhR in don… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
191
2
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 204 publications
(207 citation statements)
references
References 33 publications
12
191
2
2
Order By: Relevance
“…They are at variance with the enhanced IL-22 production and concomitant enhanced IL-17A production observed in the presence of FICZ and TCDD in the mouse [27][28][29]. TCDD was, in addition, shown to induce Treg in the mouse [25,26], whereas in our in vitro system we could not trace the emergence of Treg as far as TCDD did not upregulate the expression of FOXP3, nor the production of IL-10 and TGF-b. All together, these data stress a fundamental function of AHR in modulating the adaptive immune response with subtle but interesting differences between human and mouse T cells.…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…They are at variance with the enhanced IL-22 production and concomitant enhanced IL-17A production observed in the presence of FICZ and TCDD in the mouse [27][28][29]. TCDD was, in addition, shown to induce Treg in the mouse [25,26], whereas in our in vitro system we could not trace the emergence of Treg as far as TCDD did not upregulate the expression of FOXP3, nor the production of IL-10 and TGF-b. All together, these data stress a fundamental function of AHR in modulating the adaptive immune response with subtle but interesting differences between human and mouse T cells.…”
Section: Discussioncontrasting
confidence: 70%
“…AHR binds to, and is activated by a range of structurally divergent chemicals including natural dietary, endogenous ligands, and synthetic environmental agents among which dioxin (2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD)) is the most extensively studied pure agonist [23,24]. In the mouse, AHR is reported to regulate Th17 and Treg differentiation in ligand-specific fashion [25][26][27] and natural AHR agonists favor Th17 differentiation in vitro and enhanced IL-22 production [27][28][29][30]. Human lymphocytes may, however, behave differently and in a recent report AHR agonists appear to favor IL-22 but not IL-17 production [31].…”
Section: Introductionmentioning
confidence: 99%
“…T reg play an important role in the prevention of autoimmune disease and the regulation of immune responses to bacteria, tumors, and in GVH responses (63,64); however, the role of T reg in CD8 ϩ T cell responses during viral infection is less clear (65). Nevertheless, it was shown recently that in the context of a GVH response, AhR activation by TCDD stimulated a CD4 ϩ CD62L low CD25 ϩ subpopulation that expresses glucocorticoid-induced TNF receptor and CTLA-4, suggesting a role for T reg in TCDD-mediated suppression of CD8 ϩ T cell responses (66).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, it has been recently reported that Ahr is a ligand-dependent E3 ubiquitin ligase (21), implying that Ahr has dual functions in controlling intracellular protein levels, serving both as a transcriptional factor to promote the induction of target proteins and as a ligand-dependent E3 ubiquitin ligase to regulate selective protein degradation. It has been reported that Ahr activated by ligands such as 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD) regulates the generation of regulatory T cells (Treg) and modulates the Th1/Th2 balance (22,23). However, little is known about the molecular mechanism of how Ahr is involved in immune regulation.…”
mentioning
confidence: 99%